Women Caring for Our Aging in Place Seniors Will Lose Out because of U.S. Immigration Policies. Issue 3 (27th May 2019) - Golant, Stephen M.
ABSTRACT: Most older people experiencing chronic health problems, physical disabilities, and memory losses are still able to age in place in their own homes. However, they often need help from others to enjoy healthy, active, and independent lives. They turn mostly to family members, mainly women and usually their daughters, daughters-in-law or wives. But caring for frail elders has become more demanding and complex, and these family members often feel physically and emotionally overwhelmed and burnt out. They concede that they cannot do it alone. Others find it more difficult to hold full-or even part-time jobs. Hiring home (direct) care workers to assist their loved ones can be an effective solution to ease their caregiving responsibilities. However, these personal care aides, home health aides, and nursing assistants are already in short supply. Moreover, going forward the aging of the baby boomer population will result in an even greater demand for their services even as these jobs are often unattractive to American-born workers and turnover is high. This country's immigration policies will make it even more difficult for women caring for older persons to hire these workers. Over 25 percent of home care workers are low-skilled immigrants or foreign-born. However, the Trump administration's policies reduce the number of immigrants entering the U.S. and specifically choke off the various pathways that enable low-skilled persons to be hirable in the home care sector. Female caregivers seeking relief from their caregiving responsibilities will lose out unless we remove these immigration barriers.